SPENDING BEHAVIOR: REPURCHASE INTENTION FOR ONLINE SHOPPERS - Memarista, Gesti; Wijaya, Valentino Justin (Fakultas Bisnis Universitas Katolik Widya Mandala Surabaya, 2024)
The phenomena of online purchasing caused a rise in spending behavior. It was aided by the advancement of information technology, particularly the Internet. Electronic commerce creates an opportunity for numerous enterprises and consumers to respond by repurchasing products. An easy approach to get to the product, psychologically to follow the trend value, and a lower price from e-commerce would encourage customers to spend money to repurchase their favorite things. Based on that explanation, this research investigates the factors that drive the repurchase intention of online shoppers. The factors consist of electronic word of mouth (e-WOM), perceived convenience, and perceived value. The research’s sample was 188 respondents spreading online questionnaires in Indonesia. The findings reveal that perceived convenience and perceived value significantly affect the repurchase intention, yet electronic word of mouth (e-WOM) does not significantly affect the repurchase intention. In addition, perceived convenience significantly affects the perceived value, and the perceived value affects the electronic word of mouth significantly. The results emphasized the elements of spending behavior and would suggest the quality of the online platform should pay attention to it. So, the marketers will be able to make a reliable marketing approach to conduct the online business with compulsive buying by online shoppers.